STRATEGI PENGELOLAAN WISATA PANTAI BERBASIS KESESUAIAN DAN DAYA DUKUNG DI KAMPUNG PENYU KABUPATEN KEPULAUAN SELAYAR - Nurul Ulfa Haerani; Muhammad Kasnir; Asbar Asbar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2019)
Beach tourism is one of the favorite attractions of the community, especially in Indonesia. Aside from being cheap, Indonesia's 70% natural condition is the oceans and coastal areas that make coastal tourism appear a lot. The tourism object of the Turtle Village is located in the Tulang Village of Barugaiya District in Selayar Island Regency. From the results of research and data processing on the Analysis of Potential Kampung Penyu areas for coastal tourism areas by conducting direct observations and quantitative descriptive methods through scoring that is high potential. For Conformity Value of Coastal Tourism by looking at a number of variables from 3 location points, the results show that the area is very suitable for coastal tourism activities. For carrying capacity or carrying capacity, location 1 can accommodate around 889 people / day for coastal tourism activities, location 2 can accommodate 816 people / day for beach tourism activities and location 3 can accommodate 351 people / day for beach tourism activities. By looking at the potential, suitability and carrying capacity, a Regional Development Strategy can be formulated, namely the need to socialize to the community the community's readiness to develop areas other than coastal tourism areas but also ecotourism and culture. This can be done using the Focus Group Discussion (FGD) between communities and StakeHolder to find obstacles, and problems that hinder the development and development of tourism areas generally in Bontomanai Sub-District and especially in Kampung Penyu Areas.